ANALISIS PENGARUH VARIAN MODEL PROPAGASI TERHADAP KOMUNIKASI DATA PADA PROTOKOL ROUTING TORA, MDART DAN ZRP DI JARINGAN VANET (STUDI KASUS PETA JALAN KOTA PRAYA DAN BYPASS LOMBOK) - Priya Tama Sugara; Andy Hidayat Jatmika; Ariyan Zubaidi (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2020)
VANET is part of the Mobile Ad-hoc Network (MANET), but the nodes on VANET have a higher level of mobility. Each node that moves will cause network activity (topology changes) such as route search and message sending handled by each node. So that each node must have a routing protocol to facilitate communication in the network. The selection of the appropriate routing protocol is needed in urban and rural scenarios.This study aims to determine the effect of propagation model variants on data communication on the TORA, MDART and ZRP routing protocols on the VANET network on the Praya City and Bypass Lombok road maps with an area of ​​1000x1000 m2. For the variation of the routing protocol using four variations of the propagation model, namely the freespace propagation model, tworayground, shadowing, and nakagami. The number of nodes used in the Praya City road map is 35, 55, 70 nodes and in Lombok Bypass 25, 40, 60 nodes. The test parameters used are throughput, packet delivery ratio and end to end delay.In an urban scenario with an area of ​​1000x1000 m2, the TORA protocol gets a very good throughput parameter on nakagami propagation of 40.95 Kbps and on the ZRP protocol the value of the freespace propagation parameter PDR is 100%. While in the rural scenario a good value is obtained in freespace propagation is 4.82 second. Keywords: VANET, Routing Protocol, Propagation, NS2